The Phenomenon of Downshifting in Central and Eastern European Countries: Case Studies from Poland, the Czech Republic, and Slovakia - Duda, Aneta (Journal of Economic Sociology, 2020)
The article introduces discussions of sociocultural post-material practices that are connected with downshifting and with efforts to thrive in the shadow of dominating forms in contemporary societies. The author extends her conceptual framework beyond ecology, sociology, and the politics of sustainable lifestyles and draws from Anthony Giddens’s “reflexive project of the self.” The introduced notion of “experiencing downshift” is understood as the reflexiveexperience by those individuals, who reshape their lives to reflect its “authentic” meaning, which is connected to the resignation from high material living standards. The article offers the concept of identity as central rather than peripheral to downshifting research. Following a longitudinal panel study on the processes of far-reaching and radical changes in the lifestyles of 31 downshifters, five areas were examined: motives for the change, the character of the change, reactions of others, balance of benefits and losses, and decision consistency. Findings suggest that the contested meaning of (material) life success leads to the reframing of value priorities and the reconstruction of personal and social identities. Ideals of downshift move away from productive efforts and consumption-based identities toward practices of being reflective, self-aware, and fostering well-being, which is variously characterized by harmony, pleasure, and creativity. Most of them are not unique to downshifting, but this is not (as I have emphasized) a limitation but simply a chance for the movement to get out of the frame of a politicized, radicalized critique of capitalist growth society and make consumers appreciate that what they already do could be potentially supportive of downshift transformation.